2017
DOI: 10.3389/fmars.2017.00416
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic Eukaryotes in a Meso-Eutrophic Coastal System with Marked Phaeocystis globosa Blooms

Abstract: This study explored the potential interactions and relations of the putative Symbiotic/Decomposer/Parasitic community (SymbDec) with other taxa and predominant environmental parameters in the eastern English Channel (EEC) over a 2.5 years period (32 sampling dates). The EEC is a meso-eutrophic coastal system portrayed by intense reoccurring patterns in plankton succession with blooms of the Haptophyte Phaeocystis globosa and abundant populations of colonial diatoms and dinoflagellate grazers before and after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 98 publications
(106 reference statements)
3
24
0
Order By: Relevance
“…Syndiniales is a group comprised exclusively of parasitic species that infect tintinnid ciliates, crustaceans, dinoflagellates and fish (Guillou et al, 2008). The high abundance of Syndiniales detected in this study corresponds well to the previous findings in several metabarcoding studies on planktonic microeukaryotes (Georges et al, 2014;Christaki et al, 2017), and supports the hypothesis that parasitic interactions could dominate plankton networks (De Vargas et al, 2015;Lima-Mendez et al, 2015). Otherwise, it should be aware that potentially high rRNA gene copy numbers and inactive spores could lead to overestimation on the proportion of Syndiniales (Not et al, 2009;Sassenhagen et al, 2019).…”
Section: Dominant Groups In the Surficial Water Of Thesupporting
confidence: 87%
“…Syndiniales is a group comprised exclusively of parasitic species that infect tintinnid ciliates, crustaceans, dinoflagellates and fish (Guillou et al, 2008). The high abundance of Syndiniales detected in this study corresponds well to the previous findings in several metabarcoding studies on planktonic microeukaryotes (Georges et al, 2014;Christaki et al, 2017), and supports the hypothesis that parasitic interactions could dominate plankton networks (De Vargas et al, 2015;Lima-Mendez et al, 2015). Otherwise, it should be aware that potentially high rRNA gene copy numbers and inactive spores could lead to overestimation on the proportion of Syndiniales (Not et al, 2009;Sassenhagen et al, 2019).…”
Section: Dominant Groups In the Surficial Water Of Thesupporting
confidence: 87%
“…globosa bloom period, but gradually increased to reach its highest in fall-winter. Symbionts and degraders accounted for more than one third of the OTU diversity in fall-winter [ 67 ]. Microbial eukaryote community structure and seasonal succession were similar between surveys and years for the most abundant taxonomic groups, representing the majority of reads (>90).…”
Section: Discussionmentioning
confidence: 99%
“…However, other biases due to random sampling, sequencing methods, PCR and sequencing errors might have also contributed to this disparity [ 68 ]. In addition, previous studies in the area have suggested that inter-taxa relations, rather than environmental variables, were the main drivers of microbial community structure and temporal succession [ 45 , 67 ]. These studies showed that environmental variables could explain only around 30% of microbial eukaryote succession [ 45 ], and few correlations were observed, through network analysis, between OTUs and environmental variables while correlations between microbes dominated the network [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Christaki et al [3] reported "new players in the succession scene" of the coast of eastern English Channel, and were associated with MALVs, MAST, and Cercozoa, which were also detected in our study. These new players were suggested to participate in complex interactions [7,15], shaping the spatial [7] and temporal unicellular eukaryote assemblages in the area [9]. Especially the rare microbial fraction of these assemblages appeared to be particularly active and play significant ecological roles [57].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Ramond et al [14] have attempted to link the taxonomic diversity of protistan taxa detected with HTS with 30 different traits in samples from ecosystems across the coasts of North Atlantic Ocean, suggesting that small taxa are characterized by broader taxonomic and functional diversity. Furthermore, previously underestimated trophic strategies, such as parasitism and decomposition, have been recognized as central to marine planktonic assemblage structure and ecosystem function [9,15]. In addition, the environmental effects [9,16] and biotic relationships in unicellular eukaryotic communities have been explored, using classical and modern ecological tools [17,18].…”
Section: Introductionmentioning
confidence: 99%